The Effect of the Quality of the E-Open Service System of the Population and Civil Registration Service on User Satisfaction in Bekasi City - Tata Tiara Dwi Indrianti; Hilma Mutiara Winata (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract This study aims to analyze the influence of system quality and electronic service quality on the level of user satisfaction of E-Open services in Bekasi City. This study uses a quantitative approach with a descriptive method. The sampling method applied is two-stage sampling, then analyzed using SmartPLS version 3.2.9 to analyze the relationship between variables. The research findings show that system quality has a positive and significant impact on user satisfaction, indicated by a path coefficient value of 0.566 and an F-square value of 0.364. In addition, electronic service quality is also proven to have a significant effect on user satisfaction, with a path coefficient value of 0.346 and an F-square value of 0.136. Simultaneously, both system quality and electronic service quality together have a significant influence on user satisfaction, with an F-count value reaching 703.767. These results strengthen that improvements in the overall quality of systems and electronic services can encourage increased user satisfaction. Keywords: Electronic Service Quality, E-Open, System Quality, User Satisfaction